(untitled) (Revista Pedagogia Social UFF, 2024)
We started the research in progress of the master’s degree, highlighting the right to be a child inserted into a conception of childhood that believes in the child as a subject that builds knowledge. With this thought we believe that childhood should be a place of play, enchantment and imagination in the various spaces through which children. Much of what we are began to be built in our childhood, space of several discoveries and games, beginning of construction moments and learning. We learn, we create and gradually started the construction of our personality, character, choices and opinions. We form in our families, on the street, with our neighbors, in the church and in several other social spaces, including in school. Having this very important role for the construction of values ​​and in our human formation.